Athletes` rights under the World Anti-Doping Code: A legitimate public interest? - Goldsworthy, D. (Alternative Law Journal, 2018)
World Anti-Doping Agency considers doping transgressions strict liability offences. Strict liability offences that restrict human rights may be morally justified where legitimate social interests outweigh the rights of individuals. The World Anti-Doping Agency Code is currently under review, with a revised Code expected to be issued in January 2021. This article critically examines whether the Code conforms to international human rights standards, and whether strict liability can be ethically justified on the basis that they are in the public interest. It also considers how the principles of anti-doping policy may be shaped by and for athletes through a Rawlsian critique of anti-doping regulation.